Clinico-pathological responses of sheep to graded levels of Brachiaria decumbens diets - Muniandy, Kalai Vaani; Lim, Eric Teik Chung; Reduan, Mohd Farhan Hanif; Paul, Bura Thlama; Jaapar, Mimi Syazwani; Mohd Hamdan, Muhammad Hazziq; Abdullah Jesse, Faez Firdaus (Assiut University, Faculty of Veterinary Medicine, 2021)
Brachiaria decumbens is a highly productive tropical grass used for ruminant production. However, it can cause hepatogenous photosensitization, general ill-thrift, and deaths in ruminants due to the presence of steroidal saponins. This study determined the acute and chronic clinico-pathological responses of sheep to graded levels of B. decumbens diet. A total of 30 male crossbred Dorper sheep (six-month-old) used in the study were randomly divided into three treatment groups of 10 sheep each. Treatment 1 (T1), which served as the control group, was fed with Pennisetum purpureum and concentrates, whereas Treatments 2 (T2) and 3 (T3) were fed low (10%) and high (60%) levels of B. decumbens, respectively. The study period was divided into acute (7 days) and chronic (90 days) phases. The rectal temperature, respiratory rate, heart rate, and mucous membrane color were monitored throughout the experiment. At the end of each stage, five animals were selected from each treatment group and euthanized by slaughter to collect organs for gross pathology, organ morphometric and histopathological evaluations. The treated animals did not show significant changes (p>0.05) in rectal temperature, pulse, and respiration rates throughout the study period. However, the mucous membranes were noticeably becoming pale starting from day 60 to 90 in T3 and during the chronic phase (day 90) in T2. There was no lesion or morphometric change in any organ at postmortem examination. At histopathology, both T2 and T3 exhibited mild to moderate necrosis, hemorrhage, congestion, hydropic degeneration and edema (p<0.05) in the liver and brain. In summary, this study has established that both low and high levels of B. decumbens diets cause chronic brain and liver damages in the sheep model. This study can be used for future research on the effects of B. decumbens on grazing animals.